Evaluation of the leptin receptor in human spermatozoa - Ghaedi Kamran; Tanhaei Somayeh; Tavalaee Marziyeh; Zarkesh-Esfahani Hamid; Razavi Shahnaz; Hatami-Baroogh Leila; Deemeh Mohamad; Rabiee Farzaneh; Nasr-Esfahani Mohammad (Reproductive Biology and Endocrinology, 2010)
Abstract Background Leptin, a 167 amino acid peptide hormone, profoundly effects reproduction exerting its biological effects via interaction with the leptin receptor (ObR) which is widely expressed on peripheral tissues. In this study, we have attempted to assess leptin receptor expression in the spermatozoa of fertile males and those diagnosed with male factor infertility; both at the mRNA or protein levels. Methods Semen samples were collected from fertile males and individuals with male factor infertility. In order to evaluate leptin receptor expression several techniques were utilized, including: reverse transcriptase-polymerase chain reaction (RT-PCR), immunostaining, flow cytometry, and western blotting. Mononuclear cells isolated from volunteers' peripheral blood were used as positive controls for leptin receptor expression. Results leptin receptor was noted on mononuclear cells but we were unable to detect this receptor on spermatozoa at the protein level. Leptin receptor expression was detected on peripheral blood mononuclear cells (PBMCs) as positive controls; however it was not detectable on the spermatozoa of both groups by immunofluorescence microscopy or flow cytometry. Furthermore, positive expression of the ObR long isoform as assessed by RT-PCR was observed in the sperm of only four cases, whereas expression of beta-Actin, a house keeping gene, and HspA2, a testis specific gene, was present in all cases. Conclusion The long isoform of leptin receptor may not be present on human sperm. Species difference may be accounted for diverse reproductive physiology which depends on metabolic requirement. Leptin receptor expression at the mRNA level in some individuals may be related to contamination by other cells in semen.